1998
DOI: 10.1007/s004280050172
|View full text |Cite
|
Sign up to set email alerts
|

A new view of the so-called adenoma malignum of the uterine cervix

Abstract: Adenoma malignum of the uterine cervix (mucinous type of minimal deviation adenocarcinoma, mucinous MDA), is a unique neoplasm that is difficult to diagnose owing to the deceptively benign appearance of the tumour cells. The present study was undertaken to explore the phenotypic expression of this tumour compared with those of non-neoplastic cervical tissues and of cervical carcinomas of various types. Ten cases of mucinous MDA, 50 cases with non-neoplastic cervical tissues, 13 of cervical adenocarcinoma inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
94
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 18 publications
1
94
0
Order By: Relevance
“…2,6,7 The current study has shed further light on this issue. A review of 20 cases of MDA demonstrated coexistence of LEGH/PGM with some atypical features or morphologically usual-type AIS.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…2,6,7 The current study has shed further light on this issue. A review of 20 cases of MDA demonstrated coexistence of LEGH/PGM with some atypical features or morphologically usual-type AIS.…”
Section: Discussionmentioning
confidence: 67%
“…In 1997, it was shown to have a gastric phenotype by mucin histochemistry and immunohistochemistry using HIK1083, an antibody recognizing pyloric gland mucin of the stomach. 2,3 This antibody has since then been regarded as a promising diagnostic tool for MDAs. 4,5 However, its usefulness has been in dispute and Mikami et al 6,7 have demonstrated HIK1083 reactivity in pyloric gland metaplasia (PGM) of the cervix, which was described as lobular endocervical glandular hyperplasia (LEGH) by Nucci et al 8,9 These facts have provoked controversy concerning a possible link between LEGH/ PGM and MDA, and whether gastric phenotype is specific for these two conditions.…”
mentioning
confidence: 99%
“…27,29,30,[32][33][34]36 Because of the identical mucin expression in these lesions, several investigators have suggested that metaplastic or hyperplastic glandular lesions with pyloric gland mucin could be a precursor of minimal deviation adenocarcinoma. 32,34,37 Pyloric gland metaplasia also has been described in several other organs such as the pancreas, the gallbladder and the small and large intestine. [49][50][51][52] Pathogenesis of this metaplastic change in most organs is still under discussion; however, its relationship to carcinogenesis in the pancreas has received particular attention.…”
Section: Endocervical Adenocarcinoma With Hyperplasiamentioning
confidence: 99%
“…Gastric phenotype has been described in endocervical gastric metaplasia, lobular endocervical glandular hyperplasia and minimal deviation adenocarcinomas from the findings of histochemistry and immunohistochemistry using monoclonal antibody (HIK1083) against pyloric gland mucin. [27][28][29][30][31][32][33][34][35][36] There is also speculation that hyperplastic or metaplastic glandular lesions with gastric mucin are precursors of endocervical adenocarcinoma or in situ lesions of minimal deviation adenocarcinoma when the correspondent mucin phenotype of these lesions is considered. 32,34,37 However, this is still under discussion and, to our knowledge, there has been no direct evidence to support this hypothesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation